Preoperative magnetic resonance imaging in locoregional breast cancer: Resonancia magnética preoperatoria en cáncer de mama locoregional - Aldecoa Bedoya, Franklin (2022)
Introduction. The use of preoperative magnetic resonance imaging (PMR) in patients with breast cancer is debatable, with little agreement on its usefulness above routine scans. The goal of this study was to assess comparative studies of individuals with non-advanced breast cancer who were treated with or without PMR. Methods. A search was conducted in MEDLINE/PUBMED, LILACS, and SCIELO for medical literature published between January 1, 2000 and March 31, 2021, and publications that satisfied the inclusion criteria were included. Results. There were 3,828 publications, 53 of which matched the inclusion requirements; the papers were examined, and the findings were summarized in tables. There were 46 single or multicenter retrospective and comparative investigations, three prospective, randomized, controlled trials, and four meta-analyses including patients with infiltrating ductal or lobular carcinoma or ductal carcinoma in situ. The comparative results were antagonistic and debatable; however, in the most relevant studies, it was demonstrated that PMR delays surgery; increases mastectomies and additional biopsies; increases detection of ipsilateral/contralateral disease that is not necessarily malignant; and no significant difference in the rate of loco-regional or distant recurrence was established. Conclusion. Conclusions. PMR in non-advanced breast cancer has debatable outcomes in terms of surgery type, reoperations, and progression-free survival, and it is still being studied.